THE EFFECT OF LESSON STUDY ON THE FOURTH SEMESTER STUDENTS’ DESCRIPTIVE WRITING SKILL - M. Nur Hakim; Busra Bumbungan (Journal of Indonesian Language Education and Literary, 2016)
The objective of this research was to describe the effect of the process and results of implementation of lesson study in teaching descriptive essay writing at the fourth semester students of Indonesian Language Education and Literary Studies Program. This research was a Descriptive Quantitative that described about the process and result in the learning writing descriptive esay.  Data were analyzed using descriptive statistical analysis techniques. The results showed that it was positively increased. It looks at the focus of students showed a positive attitude in following each learning cycle. In addition, the level of mastery learning achievement showed that the obtained value of 75 to the top 30 students with a percentage of 86%, while those which scored under 75 only 5 students with a percentage of 14%. It was concluded that the lesson study had a positive influence in teaching descriptive essay writing in the fourth semester students of Indonesian Language Education and Literary Studies Program.